A Novel Sandwich-type Electrochemical Aptasensor Based on GR-3D Au and Aptamer-AuNPs-HRP for Sensitive Detection of Oxytetracycline. (2017) - Liu, Su; Wang, Yu; Xu, Wei; Leng, Xueqi; Wang, Hongzhi; Guo, Yuna; Huang, Jiadong
Abstract: A novel sandwich-type electrochemical aptasensor has been fabricated and applied for sensitive and selective detection of antibiotic oxytetracycline (OTC). This sensor was based on graphene-three dimensional nanostructure gold nanocomposite (GR-3D Au) and aptamer-AuNPs-horseradish peroxidase (HRP) nanoprobes as signal amplification. The aptamer and HRP modified Au nanoparticles provide high affinity and ultrasensitive electrochemical probe with excellent specificity for OTC.